2014
DOI: 10.1155/2014/357826
|View full text |Cite
|
Sign up to set email alerts
|

Gout Initially Mimicking Rheumatoid Arthritis and Later Cervical Spine Involvement

Abstract: Gout is clinically characterized by episodes of monoarthritis, but if not treated properly, it can lead to a chronic polyarthritis, which may eventually mimic rheumatoid arthritis (RA). We present the case of a 59-year-old man, with a history of symmetrical polyarthritis of the large and small joints with later development of subcutaneous nodules, which was initially misdiagnosed as RA, being treated with prednisone and methotrexate for a long period of time. He complained of occipital pain and paresthesia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Plain films sometimes appear false negative especially in the early stages and subsequent bone changes are advantageous but nonspecific feature of spinal gout [4, 6, 7, 11]. CT can help visualize the bone and soft tissue changes caused by tophi which appear as low-density area [6, 7, 9, 10]. The typical appearance related to these changes is characterized by punched-out erosion and well-defined margins without surrounding infiltrative changes; structures of vertebrae and endplates can remain unaffected and wedging changes of vertebral bodies are hardly seen [610].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plain films sometimes appear false negative especially in the early stages and subsequent bone changes are advantageous but nonspecific feature of spinal gout [4, 6, 7, 11]. CT can help visualize the bone and soft tissue changes caused by tophi which appear as low-density area [6, 7, 9, 10]. The typical appearance related to these changes is characterized by punched-out erosion and well-defined margins without surrounding infiltrative changes; structures of vertebrae and endplates can remain unaffected and wedging changes of vertebral bodies are hardly seen [610].…”
Section: Discussionmentioning
confidence: 99%
“…CT can help visualize the bone and soft tissue changes caused by tophi which appear as low-density area [6, 7, 9, 10]. The typical appearance related to these changes is characterized by punched-out erosion and well-defined margins without surrounding infiltrative changes; structures of vertebrae and endplates can remain unaffected and wedging changes of vertebral bodies are hardly seen [610]. MRI appears to be sensitive but nonspecific for the diagnosis of spinal gout, but MRI has an obvious advantage in manifesting abundant information of soft tissue in or around the gouty lesion [1921].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fraser et al [ 6 ] reported a case of confirmed tophaceous gout of the odontoid process that was managed successfully with allopurinol and colchicine alone. It is important to distinguish gouty arthropathy from rheumatoid arthritis as they may mimic one another clinically but the medical management is distinctly different [ 7 ]. Early involvement of the rheumatology team will help ensure that the appropriate medical management is initiated.…”
Section: Discussionmentioning
confidence: 99%